Interfacial Rheological Property and Rheokinetics of a Novel Photoreversible Micellar System. Issue 2 (1st February 2016) - Chen, Jie; Fang, Bo; Yu, Licheng; Li, Kejing; Yang, Mo; Ma, Ming
Abstract : A new photorheologically reversible micelle composed of a polymerizable cationic surfactant N -cetyl dimethylallyl ammonium chloride (CDAAC) and trans -4-phenylazo benzoic acid ( trans -ACA) was prepared. Exposing the CDAAC/ trans -ACA (14 mM/10 mM) micellar system to the UV light (365 nm) resulted in a decrease in the relative viscosity, and in turn, the relative viscosity increases to its initial value when the micellar system was exposed to visible light (460 nm), which is caused by the photoisomerization of ACA. The interfacial tension and modulus of the micellar system change significantly after UV irradiation and show the reversible interfacial rheological properties when irradiated by visible light. Furthermore, for the first time the dynamic changing of the rheological properties, i.e., the decreasing of viscosity and viscoelasticity during the UV irradiation, has been studied and well described by a rheokinetics model. GRAPHICAL ABSTRACT: